Bioremediation of coking contaminated soil: Mn(II)-oxidizing bacteria (MnOB) boost the degradation of high-molecular-weight polycyclic aromatic hydrocarbons (PAHs) - Wang, Xueqin; Wang, Ya-nan; Yan, Yidan; Liu, Yuxin; Wang, Huawei; Yang, Yuewei; Liu, Yuanwen; Sun, Yingjie; Zhao, Jianwei; Gao, Ying (Frontiers in Microbiology, 2025)
IntroductionThe Mn(II) oxidizing bacteria (MnOB) process plays an important role in persistent organic pollutant remediation, but its performance in high-molecular-weight polycyclic aromatic hydrocarbons (PAHs) degradation remains unclear.MethodsIn this study, the key role of MnOB under various nitrogen conditions in enhancing the degradation of high-molecular-weight PAHs in contaminated soil after KMnO4 pre-oxidation was investigated.Results and discussionThe results indicated that the combination of MnOB and potassium nitrate stimulation with a C/N ratio of 100:15 was effective in degrading high-molecular-weight PAHs. 80.59% of the total PAHs and 83.77% of benzo[a]pyrene (BaP) were degraded. MnOB can effectively utilize available Mn(II) to form biogenic Mn oxides (BMOs), and the amorphous Mn oxides generated by MnOB were primarily responsible for degrading high-molecular-weight PAHs. The synergistic effect of MnOB and exogenous nitrogen was conducive to the growth and proliferation of PAH-degrading bacteria in the soil. The key functional genes involved in Mn transformation (mntABC), Mn oxidation (copA, poxB, ccmC, and opuBD), nitrate/nitrite reduction (napA, narG, and nirD), and PAH degradation (pht3, pcaH, and pcaG) showed strong positive correlations. The MnOB primarily drove the formation of BMOs, whose oxidative capacity was sustained via coupling with nitrate reduction, thereby enabling continuous abiotic and biotic degradation of PAHs throughout the biogenic Mn(II) oxidation process. This study provides a feasible method for promoting the remediation efficiency of high-molecular-weight PAHs in coking contaminated soil.